Securing microservices : protect sensitive data in transit and at rest. (O'Reilly Media, Inc., 2018)
Microservice architectures offer a lot of advantages: making it easier to scale your application and team, use different technology, and ship features more quickly. However, they also create serious challenges, such as how to properly ensure that the systems you create are secure. If done well, microservice architectures can be significantly more secure than other types of software, but if approached in a naive fashion, you can end up with a less secure, more compromised system. This video provides the sophisticated knowledge you need to create secure architectures from the ground up. The course works best for participants who understand what microservices are and who have some experience working with distributed systems. Discover the best framework to use when considering the security aspects of microservices Learn how to handle authorization and authentication, transport security, and patch hygiene Explore new technologies that help implement secure distributed systems in easier ways After spending time at multiple startups and 12 years at ThoughtWorks, Sam Newman is now an independent consultant. Specializing in microservices, cloud, and continuous delivery, Sam helps clients around the world deliver software faster and more reliably. An in-demand speaker at O'Reilly Media's Software Architecture and Security conferences, Sam is the author of multiple O'Reilly Media titles, including Building Microservices and Microservices at Scale.